INTEGRASI MICRO-LEARNING DALAM PENDIDIKAN BIOLOGI UNTUK PENGUATAN LITERASI SAINS DAN NUMERASI - I Nengah Suka Widana (Program Studi Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2026)
This article aims to comprehensively examine the integration of micro-learning in biology education and its implications for strengthening scientific and numeracy literacy. The writing method employed is a literature review. A total of 47 scientific literature sources (reference books, national journals, and relevant international journals) were analyzed using thematic analysis techniques. Thematic analysis was conducted to identify patterns, themes, and conceptual meanings related to the role of micro-learning in biology learning in the digital era. The synthesis results indicate that: (1) micro-learning is an innovative pedagogical approach that is modular, focused, flexible, and learner-centered, thereby improving effectiveness, engagement, and learning retention; (2) in biology learning, micro-learning functions as a deep learning technique that acts as cognitive scaffolding, encourages concept exploration, strengthens meaningful understanding, and supports active learning; and (3) micro-learning significantly contributes to strengthening scientific and numeracy literacy through gradual concept presentation, increased motivation, reinforcement of critical thinking, and the ability to interpret data and scientific phenomena. Despite its considerable potential, the implementation of micro-learning still faces challenges, particularly related to teacher readiness, content design quality, and technological infrastructure limitations. However, with policy support, continuous training, and integration with instructional models such as blended learning and flipped classroom, micro-learning has the potential to become a transformative and sustainable learning strategy. Overall, micro-learning is not merely a technical innovation but a comprehensive pedagogical approach capable of reconstructing biology learning to be more meaningful, inclusive, and relevant to 21st-century demands.